PRACTICING INDIVIDUAL MICRO TEACHING BY APPLYING POLITENESS STRATEGIES - Agung Budi Kurniawan; Saptanto Hari Wibawa (LPPM Press STKIP PGRI Pacitan, 2014)
This research area is about practicing individual micro teaching by applying politeness strategies. There are some politeness strategies, and one of those are Face Threatening Acts or FTAs. Face Threatening Acts/ FTAs are kinds of facial expressions and gestures. Researchers assume that FTAs is very valuable and useful to be applied for micro teaching training. It is proven in this research. The micro teaching kind for this research paper is individual micro teaching. Researchers applied one shot case study of experiment research without control group. The researchers analyze the micro teaching practice through descriptive qualitative technique. There are not comparison techniques. Researchers just gave some treatments to subjects, then observed the application of the treatments. The findings and discussion are presented together in form of analysis tables in this paper. It is to analyze micro teaching performance one by one of all subjects of this research. In order to the research, the researchers hang on Brown and Levinson’s concepts of FTAs. Other additional theories and concepts also include to support them.